2020
DOI: 10.1108/bepam-12-2019-0140
|View full text |Cite
|
Sign up to set email alerts
|

Improving clients’ satisfaction in construction projects: the case of Saudi Arabia

Abstract: PurposeClients’ satisfaction is often associated with performance in the construction industry. Organisations that achieve very high ratings of clients’ satisfaction improve their positions in the marketplace. Many clients are often dissatisfied with their project outcomes. Hence, a research study was carried out to examine the ways project managers and/or contractors perceive the subject of clients’ satisfaction.Design/methodology/approachThe study applied qualitative research methods and followed the interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…"They do not consult us", a former college Dean complained. This resulted in lack of ownership or exaggerations in showing ownership by imposing changes to designs and construction sites that were costly and exposed the projects to overruns from the very beginning, as can be read in the case studies, and in line with Mitra and Wee Kwan Tan (2012) and Alshihre, et al (2020).…”
Section: Project Initiationmentioning
confidence: 84%
See 2 more Smart Citations
“…"They do not consult us", a former college Dean complained. This resulted in lack of ownership or exaggerations in showing ownership by imposing changes to designs and construction sites that were costly and exposed the projects to overruns from the very beginning, as can be read in the case studies, and in line with Mitra and Wee Kwan Tan (2012) and Alshihre, et al (2020).…”
Section: Project Initiationmentioning
confidence: 84%
“…They found that project efficiency is 60% correlated with stakeholder satisfaction and 56% with overall project success. To contribute to improving clients' satisfaction in construction projects in Saudi Arabia, Alshihre, et al (2020) identified prominent factors that impact clients' satisfaction: effective financial management, use of skilled workers, use of advanced technology, customer relation, and time management. Effective team leadership, project monitoring, communication and adequate knowledge and skills contribute to clients' satisfaction.…”
Section: Contributors To Poor Project Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…When the results about client satisfaction are compared with the previous studies’ findings, many similarities exist. In the previous studies, cost management was identified as a factor with high significance on client satisfaction (Alshihre et al, 2020; Soetanto et al, 2001). The same factor was identified as one of the major factors predicting post-occupancy overall satisfaction in the current study as well.…”
Section: Resultsmentioning
confidence: 99%
“…Azimi and Esmaeilzadeh (2017) investigated the relationship between house type and residential satisfaction via a survey using a questionnaire and found that a significant relationship existed between house type and residential satisfaction. Alshihre et al (2020) identified five main factors that the project managers perceived to have a significant impact on clients' satisfaction. These factors were effective financial management, use of advanced technology, having skilled workers, time management, and customer relation.…”
Section: Literature Reviewmentioning
confidence: 99%